1989
DOI: 10.1128/jb.171.3.1718-1724.1989
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a gene for indole-3-acetamide hydrolase from Bradyrhizobium japonicum

Abstract: A pLAFRl cosmid genomic library of wild-type Bradyrhizobiumrjaponicum J1063 was const e. A cosmid clone designated pJjJ4, containing a 26-kilobase (kb) DNA It has been shown that bacterial production of the phytohormone indoleacetic acid (IAA) is involved ih the virulence df several interactions between microorganisms and plants (19). Several pathways have been reported for the conversion of tryptophan to IAA in bacteria (27). The best-studied pathways involve conversion via indole-3-acetamide (IAM) (the IAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In the symbiotic bacteria Rhizobium fredii and Bradyrhizobium japonicum, the production of IAA via the IAM pathway was suggested, as bacterial cultures can convert an IAM analog. A gene (bam) with sequence similarity with iaaH could be isolated from B. japonicum (Sekine et al 1988;Sekine et al 1989). Later, the presence of the IAM pathway was also confirmed for Rhizobium sp.…”
Section: Indole-3-acetamide Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In the symbiotic bacteria Rhizobium fredii and Bradyrhizobium japonicum, the production of IAA via the IAM pathway was suggested, as bacterial cultures can convert an IAM analog. A gene (bam) with sequence similarity with iaaH could be isolated from B. japonicum (Sekine et al 1988;Sekine et al 1989). Later, the presence of the IAM pathway was also confirmed for Rhizobium sp.…”
Section: Indole-3-acetamide Pathwaymentioning
confidence: 99%
“…In the first step tryptophan monooxygenase (encoded by iaaM gene) converts tryptophan to IAM; in the second step IAM is hydrolyzed to IAA and ammonia by an IAM hydrolase (encoded by iaaH gene). Both genes have been characterized from many phytopathogens such as Agrobacterium tumefaciens, P. savastanoi, Pseudomonas syringae, Pantoea agglomerans, but also in symbiotic nitrogenfixing bacteria belonging to Rhizobium and Bradyrhizobium species (Sekine et al 1989;Clark et al 1993;Morris 1995;Theunis et al 2004). In A. tumefaciens, these genes are located in the T-DNA region of the pTi plasmid together with the ipt gene (coding for dimethylallylpyrophosphate:AMP dimethylallyltransferase), involved in cytokinin production (for reviews see Hooykaas and Beijersbergen 1994;Costacurta and Vanderleyden 1995).…”
Section: Indole-3-acetamide Pathwaymentioning
confidence: 99%
“…A gene encoding for one of the enzymes in the IAA biosynthetic pathway has been identified in Bradyrhizobiumjaponicum (26). Phytohormones are also implicated in the Rhizobium infection process and nodule morphogenesis, and nodules are known to contain much higher levels of cytokinins than root tissue (7), but to date no Rhizobium genes or genetic loci directly involved in cytokinin biosynthesis or in the maintenance of hormonal balance have been identified.…”
mentioning
confidence: 99%
“…This indicated that the biosynthesis of IAA was adjusted for the expression on the different environment. Bacterias which employed IAM pathway in synthesizing IAA were Agrobacterium tumefaciens (Morris, 1995), Bradyrhizobium (Sekine et al, 1989), Pseudomonas syringae, Pantoea agglomerans, dan Rhizobium (Sekine et al, 1989;Theunis et al, 2004;Spaepen et al, 2007).…”
Section: Detection Of Tryptophan Monoxigenase (Iaam) Gene On Streptommentioning
confidence: 99%
“…The two main biosynthetic pathways of IAA were indole-3-acetamide (IAM) and indole-3-pyruvate (IpyA). The former has been identifi ed on Bradyrhizobium japonicum dan Rhizobium fredii (Sekine et al, 1989), Azospirillum brasilense (Bar and Okon, 1993), Agrobacterium tumefaciens and Pseudomonas savastanoi (Comai and Kosuge, 1982;Yamada et al, 1985) and Streptomyces spp. (Manulis et al, 1994).…”
Section: Introductionmentioning
confidence: 99%